Las Cargas: Characterization and Prehistoric Use of a Southern Andean Obsidian Source. Issue 2 (6th February 2015) - Salgán, Laura; Garvey, Raven; Neme, Gustavo; Gil, Adolfo; Giesso, Martín; Glascock, Michael D.; Durán, Víctor
<x xml:space="preserve">Abstract</x> The importance of obsidian from the northern Patagonian source at Las Cargas is reflected in its early use (∼8000 years B.P.) and extensive geographic diffusion but is nonetheless surprising in light of the source's high altitude (located in the Andes Cordillera), which makes it both difficult to access under ideal conditions and inaccessible for much of the year. Prehistoric use of the Las Cargas source can inform us about mobility, subsistence choices, economics of stone consumption, trade, and territoriality. Here we present the results of various lines of evidence (surface survey, X‐ray fluorescence and instrumental neutron activation analyses, artifact morphometry, and obsidian hydration dating) used to characterize obsidian from Las Cargas and its prehistoric use during the Holocene. Results indicate that Las Cargas obsidian occurs at the source as blocks and nodules, which are chemically homogeneous and of variable quality. Use of the source was nearly continuous through time, and the primary knapping activities performed there were the production of blanks and preparation of cores.